MORAL DILEMMAS IN REAL LIFE Current Issues in Applied Ethics - EZRA, OVADIA; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
Moral Dilemmas in Real Life purports to supply ways of thinking of, perhaps even dealing with, the ins and outs of ethical argument.such argument. The world today presents both individuals and communities with situations, which demand moral and ethical deliberations. From the more general issues of universal globalization to the very specific problems of every-day existence encountered by active agents, contemporary life is replete with moral and ethical conundrums. Any thinking person is required, so it seems, to be concerned, involved, or - at the very least - conversant with these issues and this book supplies the wherewithal needed. Applied ethics is that intellectual locale where theory meets praxis. Moral Dilemmas in Real Life is designed to make that meeting point explicit, by presenting a series of issues in well-grounded philosophical formulations. The book begins with the general relation between the individual and society - instilling ethical tension, and even clashes, between the private and the public in our discourse. Going on, from general to specific, it gradually narrows the ethical playing field to touch on medical ethics, the family, and the practice of punishment. In all cases, the book addresses both consensual and conventional social institutions and distortions thereof.
INDIVIDUAL RIGHTS AND PUBLIC DUTIES -- PRIVACY AND THE PUBLIC SPHERE -- THE OBLIGATION OF THE STATE TOWARD INDIVIDUALS -- PUBLIC SECURITY VS. THE RIGHT TO "BE LET ALONE" -- FREEDOM OF EXPRESSION IN ACADEMIA AND THE MEDIA -- MEDICAL ETHICS -- MERCY DEATH OR KILLING -- DONATING OR SELLING ORGANS -- GENETIC ENGINEERING AND REPRODUCTION -- PARENTHOOD AND THE FAMILY -- RIGHTS OF RELATIVES AND GENERATIONS -- PROCREATION AFTER DEATH -- BABIES AS COMMODITIES -- PUNISHMENT -- PUNISHMENT OF SEX OFFENDERS -- PUNISHMENT AND DOMESTIC VIOLENCE -- CAPITAL PUNISHMENT AND THE MENTALLY RETARDED.
Keywords: PHILOSOPHY (GENERAL).; ETHICS; PHILOSOPHY OF LAW; MEDICINE -- PHILOSOPHY; TECHNOLOGY -- PHILOSOPHY; POLITICAL SCIENCE -- PHILOSOPHY; PHILOSOPHY; ETHICS; PHILOSOPHY OF LAW; POLITICAL PHILOSOPHY; PHILOSOPHY OF MEDICINE; PHILOSOPHY OF TECHNOLOGY